(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Oronyms is a branch of toponymy that studies various forms and names and is one of the less developed branches of onomastic sciences. The analysis of the learning aspects of Oronims is an important tool in solving many problems of linguistics, history, ethnography and geography, and allows obtaining a number of valuable information and scientific evidence.